A simple lesson plan for the course English Composition II - Córdoba Cubillo, Patricia (2005)
The goal of this article is to present a lesson plan and a series of   sample tasks to help the instructors  from the course English Composition II,  at the School of Modern Languages from the University of Costa Rica, to guide students write  an essay integrating the four skills: listening, speaking, reading, and writing.  These activities will be a source of comprehensible input for the learners that will hopefully result in a good writing piece. El objetivo de este artículo es presentar un plan de lección y una serie de actividades que le ayudarán a los y las instructoras del curso Composición Inglesa II de la Escuela de Lenguas Modernas de la Universidad de Costa Rica a guiar a sus estudiantes a escribir un ensayo integrando las cuatro macro-destrezas, a saber comprensión auditiva, conversación, lectura y escritura. Mediante estas actividades se espera que los estudiantes elaboren un ensayo de calidad.